DETEKSI DINI KANKER SERVIKS DENGAN SOSIALISASI IVA SCREENING DI KELURAHAN KANDANG MAS - Rismayani; Poppy Siska Putri; Lety Arlenty; Nurul Maulani (Fakultas Pertanian, 2023)
The high prevalence of cervical cancer is influenced by the behavior of early detection which is still low. According to the 2018 Riskesdas tumors/cancer in Indonesia showed an increase from 1.4 per 1000 population in 2013 to 1.79 per 1000 population in 2018. Cervical cancer can be detected by IVA method but the interest and motivation of women of childbearing age to do IVA examination to detect cervical cancer is still minimal. Health education needs to be done to increase the knowledge and interest of mothers (WUS) about cervical cancer. This community service activity has the aim of increasing the behavior of women in the Kandang Mas sub-district to carry out early detection of cervical cancer through the IVA method examination. The implementation method is to provide socialization or health counseling using leaflets and leaflets about the IVA method examination material and followed by a question and answer session with the participants. The results obtained from this community service activity were an increase in the knowledge and interest of women of childbearing age (WUS) in carrying out the IVA Test. In addition, the service method in the form of counseling and question and answer is very appropriate in motivating the community to be able to foster community interest and motivation, especially women of childbearing age (WUS) to carry out early detection of cervical cancer with the IVA method at the nearest health facility.